Dynamics of Bacterial Community and Fermentation Quality in Leymus chinensis Silage Treated With Lactic Acid Bacteria and/or Water - Xu, Haiwen; Sun, Lin; Na, Na; Wang, Chao; Yin, Guomei; Liu, Sibo; Xue, Yanlin (Frontiers in Microbiology, 2021)
This study aimed to reveal the bacterial community and fermentation quality of Leymus chinensis silage during fermentation process. Leymus chinensis was harvested at the heading stage, and ensiled with lactic acid bacteria (LAB, L), water (W), or a combination of both (LW) in vacuum-sealed plastic bags. The samples were taken at 0, 5, 15, 35, and 60 d after ensiling. The bacterial community structure was assessed by plate cultivation and Illumina sequencing, and the fermentation parameters were also analyzed. Fresh L. chinensis contained low moisture (509 g/kg) and LAB (3.64 log colony forming units/g fresh weight). Control silage displayed higher pH and lower lactic acid (LA) than other treatments during enslage (P < 0.05); moreover, LW-treatment had lower pH from 5 to 35 d and greater LA at 5 d than L- and W-treatments (P < 0.05). During fermentation process, Lactobacillus in L- and LW-treatments was the most dominant bacterial genus (> 97%), had higher abundance than that in control silage and W-treatment (P < 0.05), and correlated negatively with other main genera and pH, and positively with LA and acetic acid (P < 0.05). Moreover, Lactobacillus had considerable abundance in W-treatment from 5 to 15 d. Enterobacteriaceae had the most abundance among bacteria in control silage during ensiling, and in W-treatment from 35 to 60 d. The L-, W-, and LW-treatments displayed the aggregated bacterial community at 5 and 15 d, with W-treatment diverging from L- and LW-treatments at 35 and 60 d. Overall, the low moisture and/or insufficient LAB in fresh L. chinensis led to Enterobacteriaceae dominating bacterial community and contributing to the high pH and low LA in control silage during fermentation process. Applying L, W, or LW contributed to Lactobacillus succession, LA production, and pH reduction during early stage of fermentation; moreover, treating with L and LW displayed more efficiency. Lactobacillus dominated the entire ensilage process in L- and LW-treatments and the early stage of fermentation in W-treatment, and contributed to the satisfactory fermentation quality of L. chinensis silage. The L- and LW-treatments displayed the similar pattern of bacterial succession during ensiling.